The Contributions of Indonesian Islam: in the Context of Socio-Cultural Identity - Wartono Wartono; Supriyono Supriyono (International Journal Ihya' 'Ulum al-Din, 2020)
This paper discusses on the contribution of Indonesian Islam in the context of socio-cultural identity. Muslim is a large social identity which represent to citizenship identification in Indonesian context. The dynamic of Indonesian Muslim that have special status is interesting to be investigated about socio-cultural identity. Actually, both in the Qur’an and the substantive level, Islam expression can be diverse. It could be considered Islamic expression of its role, character, approach and region. This paper records the results of research that has addressed the varietyproblem of Islamic identity in terms of region. The data was collected through answer method, documentation, and analyzed through content analysis. As a result, there are eight Islamic identities from the perspective of the region published in Indonesian, they are: Archipelago Islam, Indonesian Islam, Javanese Islam, Radical Islam, Islamic Sasak, Islamic Sharia, and Islam Indigenous Hatubana, Kumai Bubuhan Islamic, and Coastal Islamic. All Islamic identity is influenced by the culture and the local tradition. Only a handful of variants that the identity is rather keep a distance with the local culture and tradition, five times in Islamic Sasak, Islamic Sharia in Hatubana and Nabu Group in Kumai Bubuhan Islamic. The result describes that Muslim construct their citizenship identity with extending of Islamic teaching categorization and education in both of cultural and national. That is against to Turner’s opinion which said that citizenship will be luck by religious identification. Furthermore, Indonesian Muslim have been met of the citizenship identity as a transformative process from primordial categorization into inclusive categorization